The role of metabolism in bacterial persistence - Amato, Stephanie M.; Fazen, Christopher H.; Henry, Theresa C.; Mok, Wendy W.; Orman, Mehmet A.; Sandvik, Elizabeth L.; Volzing, Katherine G.; Brynildsen, Mark P. (Frontiers in Microbiology, 2014)
Bacterial persisters are phenotypic variants with extraordinary tolerances toward antibiotics. Persister survival has been attributed to inhibition of essential cell functions during antibiotic stress, followed by reversal of the process and resumption of growth upon removal of the antibiotic. Metabolism plays a critical role in this process, since it participates in the entry, maintenance, and exit from the persister phenotype. Here, we review the experimental evidence that demonstrates the importance of metabolism to persistence, highlight the successes and potential for targeting metabolism in the search for anti-persister therapies, and discuss the current methods and challenges to understand persister physiology.